2007
DOI: 10.1111/j.2006.0030-1299.15586.x
|View full text |Cite
|
Sign up to set email alerts
|

Extinctions in competitive communities forced by coloured environmental variation

Abstract: Understanding the relationships between environmental fluctuations, population dynamics and species interactions in natural communities is of vital theoretical and practical importance. This knowledge is essential in assessing extinction risks in communities that are, for example, pressed by changing environmental conditions and increasing exploitation. We developed a model of density dependent population renewal, in a Lotka–Volterra competitive community context, to explore the significance of interspecific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 42 publications
(76 reference statements)
2
43
2
1
Order By: Relevance
“…This was most probably due to a failure of the linearization techniques employed in the analytical derivation to capture population variation under strong environmental forcing. This work generalizes the results from previous reports (Ripa & Ives 2003;Ruokolainen et al 2007) and extends our knowledge of the behaviour of multi-species competitive communities in variable environments.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…This was most probably due to a failure of the linearization techniques employed in the analytical derivation to capture population variation under strong environmental forcing. This work generalizes the results from previous reports (Ripa & Ives 2003;Ruokolainen et al 2007) and extends our knowledge of the behaviour of multi-species competitive communities in variable environments.…”
Section: Introductionsupporting
confidence: 90%
“…One interesting feature is that with overcompensatory population dynamics, increasing noise autocorrelation can lead to a decrease in EP (Petchey et al 1997;Schwager et al 2006;Ruokolainen et al 2007). We have shown here that this result arises due to the way environmental noise is amplified in the community dynamics, under different regimes of environmental forcing.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Recent evidence from a study of bacterial diversity has highlighted high levels of ecotype diversity 15 within the same bacterial clades (Koeppel et al, 2008), further emphasizing the need to understand functional relationships within a trophic level (Berlow et al, 2004). Previous theoretical work has shown that variation in species intrinsic growth rate in the community may (Ruokolainen et al, 2007) or may not (Fowler and Lindström, 2002) lead to qualitative differences in community responses following different disturbances in simulated 20 competitive communities. These two studies only examined under-and/or damped overcompensatory dynamics in the stable equilibrium range.…”
Section: Introductionmentioning
confidence: 99%